NOVEL NGRESTITI ATI: ANALISIS PSIKOLOGI SASTRA - Padmasari, Ida Ayu Ratu (Humanis, 2014)
The study is titled "A Novel Ngrestiti Ati Psychological Analysis of Literature" that discusses modern Balinese literary novels shaped by the study of the structure and psychology literature. This study aimed to describe the structural aspects and psychological aspects of the novel Ngrestiti Ati. Teori figures used in this study is the structural theory by Teeuw and personality psychology Sigmund Freud. Methods and techniques in this study consists of three phases namely, the provision of data, data analysis, and presentation of data analysis. In Phase providing data used refer to the method, assisted with technical notes and translation techniques. Phase used qualitative methods of data analysis and descriptive analytic techniques. In the presentation phase of data analysis used informal methods of inductive and deductive techniques. The results achieved in this study reveals a novel structure that includes four Ngrestiti Ati incident, the grooves flashback, the main character, secondary character, and the complementary character, place setting, time setting, the atmosphere and the background, theme and mandate. Besides, this study also reveals the psychological aspects of characters that includes the Ngrestiti Ati Novel Id, Ego, and Superego.
Keywords: novel, structure, psychology